Down-regulation of UCRP and UBE2L6 in BRCA2 knocked-down human breast cells - Tripathi, Manish K. (2005)
To understand the effects of the transient ablation of BRCA2 gene expression in dividing human breast cells we transiently knocked down BRCA2 mRNA in HMEC and other cells. Microarray analysis of mRNAs revealed the down-regulation of the mRNAs of ubiquitin cross-reacting protein (UCRP) and the E2 enzyme that help conjugating UCRP to its target proteins, namely UBE2L6 (UbcH8), in BRCA2 ablated cells. UCRP is an interferon regulated protein, involved in cell growth and cell cycle events by participating in the degradation/modulation of cell cycle regulatory proteins. Quantitative-PCR and Northern analysis confirmed down-regulation of UCRP and UBE2L6 with BRCA2 knock down, respectively. Since UCRP and UCRPylation have critical roles in the innate immunity against viral infection and during pregnancy, our observation may indicate new roles of the BRCA2 protein.